Food security : indicators, measurement, and the impact of trade openness - Guha-Khasnobis, Basudeb; Acharya, S. S.; Davis, Benjamin, 1964-; World Institute for Development Economics Research (Oxford : Oxford University Press, 2007)
The fight against world hunger has recently been overshadowed by the drive to end poverty. Yet the growing importance of the WTO and its role in shaping the agricultural trade agenda, has serious implications for food security across the globe. This volume attempts to redress the balance and provide a much needed debate on this topic.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Food supply -- Developing countries; Food supply -- Research; Produce trade -- Developing countries